High-dose rifamycins in the treatment of TB: a systematic review and meta-analysis. Issue 12 (7th January 2022) - Arbiv, Omri A; Kim, JeongMin M; Yan, Marie; Romanowski, Kamila; Campbell, Jonathon R; Trajman, Anete; Asadi, Leyla; Fregonese, Federica; Winters, Nicholas; Menzies, Dick; Johnston, James C
Abstract : Background: There is growing interest in using high-dose rifamycin (HDR) regimens in TB treatment, but the safety and efficacy of HDR regimens remain uncertain. We performed a systematic review and meta-analysis comparing HDR to standard-dose rifamycin (SDR) regimens. Methods: We searched MEDLINE, Embase, CENTRAL, Cochrane Database of Systematic Reviews and clinicaltrials.gov for prospective studies comparing daily therapy with HDRs to SDRs. Rifamycins included rifampicin, rifapentine and rifabutin. Our primary outcome was the rate of severe adverse events (SAEs), with secondary outcomes of death, all adverse events, SAE by organ and efficacy outcomes of 2-month culture conversion and relapse. This study was prospectively registered in the International Prospective Register of Systematic Reviews (CRD42020142519). Results: We identified 9057 articles and included 13 studies with 6168 participants contributing 7930 person-years (PY) of follow-up (HDR: 3535 participants, 4387 PY; SDR: 2633 participants, 3543 PY). We found no significant difference in the pooled incidence rate ratio (IRR) of SAE between HDR and SDR (IRR 1.00, 95% CI 0.82 to 1.23, I 2 =41%). There was no significant difference when analysis was limited to SAE possibly, probably or likely medication-related (IRR 1.07, 95% CI 0.82 to 1.41, I 2 =0%); studies with low risk of bias (IRR 0.98, 95% CI 0.79 to 1.20, I 2 =44%); or studies using rifampicin (IRR 1.00, 95% CI 0. 0.75–1.32, I 2 =38%). No significant differences were noted in pooled outcomes of death, 2-month culture conversion and relapse. Conclusions: HDRs were not associated with a significant difference in SAEs, 2-month culture conversion or death. Further studies are required to identify specific groups who may benefit from HDR.